Endogenous informational lobbying - David Austen-Smith (Fondazione Eni Enrico Mattei (FEEM), 1997)
The focus of this paper is on individuals' decisions to seek access to influence a legislator's policy choice from a given binary agenda under uncertainty. In the model, influence is exclusively through the provision of information regarding the true state of the world, and money is used exclusively to seek access to the legislator to exert such influence. However, bias can occur through differences in individuals' willingness to contribute to seek access and through choice of argument at the lobbying stage, conditional on access being granted. Among the results are that the decision of moderates (i.e. those with state-dependent induced preferences over the agenda) to seek access is independent of others' decisions, but this is not true of extremists (those who unequivocally favour one or other of the two alternatives); that although the policy preferences of the legislator coincide with those of the moderates, the legislator often sets the required contribution from moderates higher than that from extremists and, moreover, this is so despite the fact that extremists seeking access offer an argument to the legislator which, although informative, gives negligible payoff gains to the legislator; and, finally, that (expected) "bias« in decision making typically exists and persists even when the size of extremist groups is negligible relative to that of the moderate group.
Keywords: D72; 330; Informational lobbying; Collective action; Campaign contributions; Legislative access